High growth rate and low feed conversion ratio using new type demand feeding system with image processing program and fish behavior - Mukai, Yukinori; Taha, Zahari; Nai, Han Tan; Ismail, Khairul Muttaqin; Mohd Razman, Mohd Azraai; Adnan, Faeiz Azizi (2019)
New type feeding system was developed to overcome the various problems related to feeding to fish. This system used fish behaviour as indicator to control feeding device. In general when fish are hungry, they show some attitudes that they are searching something or looks twitchy. When fish are satisfied, their behaviour is different. In this system, CCD cameras detected fish behaviour and computer program analysed the differences of behaviour, then the programed decided and transmitted the order to feeding device to start feeding or stop feeding. This type feeding device is creative, unique and the first in the world. This system can solve various feeding problems and surely will make a revolution in aquaculture.